Deaths in Custody Reporting Program: Arrest-Related Deaths, 2003-2009 ([Verlag nicht ermittelbar], 2016)
The Arrest-Related Deaths (ARD) program is an annual national census of persons who die either during the process of arrest or while in the custody of state or local law enforcement personnel. The Bureau of Justice Statistics (BJS) implemented the ARD program in 2003 as part of the Deaths in Custody Reporting Program (DCRP). The DCRP was initiated to fulfill the data collection requirement of the Deaths in Custody Reporting Act of 2000 (DICRA, P.L. 106- 247). It collects in-depth information on deaths during arrest and incarceration, and it provides national-level information on the deaths of suspects and offenders from their initial contact with law enforcement personnel through the time they are incarcerated in a jail or prison. ARD data are collected to quantify and describe the circumstances surrounding civilian deaths that take place during an arrest or while in the custody of law enforcement. These data describe the prevalence and incidence of arrest-related deaths across the nation, identify the circumstances or activities that contribute to these deaths, and reveal trends in the causes and circumstances of these deaths in custody at national and state levels. These data can be used to inform specific policies that may increase the safety of law enforcement officers and citizens, identify training needs in law enforcement agencies, and assist in developing prevention strategies. The current ARD program relies on state reporting coordinators (SRCs) in each of the 50 states and the District of Columbia to identify and report on all eligible cases of arrest-related deaths. BJS compiles data from the states to produce national-level statistics on deaths that occur in the process of arrest by, or while in the custody of, state and local law enforcement personnel.